Thermosetting resin composition and color filter

By using a thermosetting resin composition containing an epoxy-based polymer, a polycarboxylic acid hemiacetal ester and a silicone-based surfactant in the color filter protective film, the problems of NMP permeability, low metal ion residue and insufficient coating properties at high temperatures are solved, and excellent NMP tolerance, low metal ion residue and good coating properties are achieved, and the yield and display performance of the color filter are improved.

CN119662083APending Publication Date: 2025-03-21NOF CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411300184.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-03-28
Filing Date
2024-09-18
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The existing color filter protective film cannot effectively inhibit the penetration of NMP at high temperatures, resulting in the transmission and dissolution of pigments, causing display failures; at the same time, the low metal ion residual property and coating properties are insufficient, resulting in a decrease in yield.

Method used

The thermosetting resin composition is formed by combining epoxy-containing polymers, polycarboxylic acid hemiacetal esters and silicone-based surfactants in a specific ratio range to prepare a protective film with excellent NMP resistance, low metal ion residual properties and good coating properties.

Benefits of technology

It can suppress NMP penetration at high temperatures, reduce pigment dissolution, improve low metal ion residual property and coating properties, and improve the yield and display performance of color filters.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

Provided is a thermosetting resin composition containing an epoxy compound (A), a polycarboxylic acid hemiacetal ester (B), and a silicone-based surfactant (C), the epoxy compound (A) containing an epoxy group-containing polymer having as structural units (a1), (a2) and (a3) monomers and having an epoxy equivalent weight of 155-240 g / mol, the amount of (C) being 0.01-1.0 parts by mass per 100 parts by mass of the total of (A) and (B), and the amount of the silicone-based surfactant (C) being 0.01-1.0 parts by mass per 100 parts by mass of the total of (A) and (B). The functional group equivalence ratio of the carboxyl group (B) to the total epoxy group (A) is in the range of 0.25-0.95. The thermosetting resin composition can form a cured film with excellent NMP resistance and low metal ion residue, and has good coating property at low viscosity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a thermosetting resin composition and a color filter having a protective film formed by curing the thermosetting resin composition. Background Art

[0002] The color filter used in a liquid crystal display device is generally a structure in which a black matrix layer formed into a prescribed pattern, a coloring layer in which red (R), green (G), and blue (B) are arranged in a prescribed order, a protective film, a columnar spacer (photo-spacer), and an orientation film are sequentially stacked on a transparent substrate.

[0003] Recently, the requirements for the display performance of liquid crystal displays have become increasingly stringent. For color filters, in addition to display performance such as brightness, color purity and contrast, the requirements for reliability such as the phenomenon of image fixation of display elements called burn-in or display unevenness are also increasing. According to Patent Document 1, it is believed that the occurrence of the burn-in is affected by the Na ions or K ions contained in the developer such as potassium hydroxide or sodium carbonate remaining on the surface of the protective film during the columnar spacer formation process. It is believed that these ions are easily retained due to the influence of polar functional groups such as carboxyl or hydroxyl groups, which are generated on the surface of the protective film due to pre-coating cleaning such as UV ozone treatment of the protective film surface before the columnar spacer is coated. Therefore, the protective film is required to have the ability to suppress the residue of Na ions or K ions even when it comes into contact with a developer such as potassium hydroxide or sodium carbonate after UV cleaning (hereinafter referred to as low metal ion residue). Patent Document 1 proposes a color filter protective film resin composition having excellent low metal ion residual property, which comprises a combination of an epoxy group- or oxetane group-containing polymer, a polycarboxylic acid hemiacetal ester, a specific epoxy compound, and a difunctional bisphenol A epoxy resin.

[0004] In addition, in order to improve the optical properties of the display, the color filter protective film is being thinned (film thickness after processing: about 1.0 μm), and the viscosity of the color filter protective film coating liquid is required to be low (3.0 mPa· or less). However, due to the low viscosity of the coating liquid, coating defects such as liquid return of the coating liquid or shrinkage of the coating film are likely to occur at the glass part of the substrate end, resulting in a problem of reduced yield of the color filter. In order to prevent the occurrence of such coating defects, the coating liquid for the protective film is sought to have excellent coating properties even when it is designed to have a low viscosity. As a resin composition for a color filter protective film with excellent coating properties, Patent Document 2 proposes a composition composed of an epoxy compound, an epoxy curing agent, N-alkylmorpholine, and a fluorine-based nonionic surfactant, and Patent Document 3 proposes a composition composed of a multifunctional epoxy resin, a polycarboxylic acid hemiacetal ester, and a monohydric alcohol.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Publication No. 2022-112451

[0008] Patent Document 2: Japanese Patent Application Publication No. 2011-65051

[0009] Patent Document 3: Japanese Patent Application Publication No. 2022-26360 Summary of the invention

[0010] 1. Technical issues to be resolved

[0011] In recent years, in order to expand the color gamut that liquid crystal display devices can display, the miniaturization of pigments contained in the coloring layer or the increase in pigment concentration has been promoted. However, due to its influence, the pigment will penetrate the protective film and dissolve into the liquid crystal layer, causing display failure. It is believed that the dissolution of the pigment component is produced by the solvent (N-methyl-2-pyrrolidone, hereinafter referred to as NMP) of the orientation film that penetrates into the protective film in the orientation film formation process as a post-process of the protective film. In this process, since the protective film is exposed to a high temperature of about 180°C in contact with NMP, the protective film is required to have a performance that can suppress the penetration of NMP even at high temperatures (hereinafter referred to as NMP tolerance). In addition, the previous color filter protective film is considered sufficient as long as it can suppress the penetration of the solvent under the conditions of about 25~40°C, but in order to suppress the dissolution of the above-mentioned pigment components, it is necessary to suppress the penetration of the solvent at a temperature significantly higher than before.

[0012] In addition, the amount of UV irradiation during the pre-coating cleaning of columnar spacers varies from manufacturer to manufacturer, and in particular, among manufacturers that perform high-energy UV irradiation, there are still cases where problems such as burn-in or uneven display may occur. Therefore, when performing the pre-coating cleaning of columnar spacers, it is necessary to suppress the residual Na ions or K ions even when exposed to higher energy UV light. Furthermore, with regard to coating properties, it is sought to avoid coating defects such as liquid return of the coating liquid or shrinkage of the coating film due to coating methods such as spin coating or slit coating. According to the research of the inventors of the present application, the compositions described in Patent Documents 1 to 3 are not sufficient in terms of taking into account NMP tolerance, low metal ion residue and coating properties.

[0013] The present invention has been made in view of the above-mentioned prior art, and provides a thermosetting resin composition capable of forming a cured film having excellent NMP resistance and low metal ion residual property and having good coating properties at low viscosity, and a color filter using a protective film composed of a cured product of the thermosetting resin composition.

[0014] (II) Technical solution

[0015] The inventors of the present application have conducted various studies to solve the above-mentioned technical problems, and as a result, have found that the above-mentioned technical problems can be solved simultaneously by combining a specific epoxy group-containing polymer, a polycarboxylic acid hemiacetal ester, and a silicone-based surfactant in a specific ratio range, thereby completing the present invention.

[0016] That is, the present invention is as follows [1]-[3]. [1]

[0018] A thermosetting resin composition comprising an epoxy compound (A), a polycarboxylic acid hemiacetal ester (B), and a silicone surfactant (C), wherein:

[0019] The epoxy compound (A) comprises an epoxy group-containing polymer having (a1) a (meth)acrylate monomer having an epoxy group, (a2) a monomer represented by the following formula (1), and (a3) ​​a monomer represented by the following formula (2) as structural units and having an epoxy equivalent of 155 to 240 g / mol,

[0020] [Chemical formula 1]

[0021]

[0022] In formula (1), R 1 represents a hydrogen atom or a methyl group, R 2 represents an aromatic group or an alicyclic hydrocarbon group having 3 to 12 carbon atoms,

[0023] [Chemical formula 2]

[0024]

[0025] In formula (2), R 3 represents an alicyclic hydrocarbon group or an aromatic hydrocarbon group having 3 to 12 carbon atoms,

[0026] The amount of the silicone surfactant (C) is 0.01 to 1.0 parts by mass relative to 100 parts by mass of the total of the epoxy compound (A) and the polycarboxylic acid hemiacetal ester (B).

[0027] The functional group equivalent ratio of the carboxyl groups of the polycarboxylic acid hemiacetal ester (B) to the total epoxy groups of the epoxy compound (A) is in the range of 0.25 to 0.95. [2]

[0029] The thermosetting resin composition according to [1], further comprising an organic solvent, wherein the ratio of the alicyclic ketone organic solvent in the organic solvent is 20% by mass or more and 80% by mass or less. [3]

[0031] A color filter having a protective film formed by curing the thermosetting resin composition according to [1] or [2].

[0032] (III) Beneficial effects

[0033] According to the thermosetting resin composition of the present invention, a color filter protective film having excellent NMP resistance and low metal ion residual property can be formed. In addition, the thermosetting resin composition of the present invention also has excellent coating properties at low viscosity. DETAILED DESCRIPTION

[0034] The thermosetting resin composition of the present invention contains an epoxy compound (hereinafter referred to as component (A)), a polycarboxylic acid hemiacetal ester (hereinafter referred to as component (B)), and a silicone surfactant (hereinafter referred to as component (C)).

[0035] <(A)Component>

[0036] The component (A) of the present invention includes an epoxy group-containing polymer as an essential component, wherein the epoxy group-containing polymer has (a1) a (meth)acrylate monomer having an epoxy group, (a2) a monomer represented by the following formula (1), and (a3) ​​a monomer represented by the following formula (2) as structural units and has an epoxy equivalent of 155 to 240 g / mol. The component (A) may be used alone or in combination of two or more.

[0037] [Chemical formula 3]

[0038]

[0039] In formula (1), R 1 represents a hydrogen atom or a methyl group, R 2 represents an aryl group or an alicyclic hydrocarbon group having 3 to 12 carbon atoms.

[0040] [Chemical formula 4]

[0041]

[0042] In formula (2), R 3 It represents an alicyclic hydrocarbon group or an aromatic hydrocarbon group having 3 to 12 carbon atoms.

[0043] (a1) The (meth)acrylate monomer having an epoxy group may be any (meth)acrylate monomer as long as it is an epoxy group, and any monomer known in such applications may be adopted.

[0044] Preferred examples of the (meth)acrylate monomer having an epoxy group include monomers represented by the following formulae (3) to (5).

[0045] [Chemical formula 5]

[0046]

[0047] In formula (3), R 4 represents a hydrogen atom or a methyl group, and k represents an integer of 1 to 3.

[0048] [Chemical formula 6]

[0049]

[0050] In formula (4), R 5 represents a hydrogen atom or a methyl group, R 6 represents a -CH2O- group or a -CH2- group, R 7 represents a hydrogen atom or an alkyl group having 1 to 2 carbon atoms, and m represents an integer of 1 to 3.

[0051] [Chemical formula 7]

[0052]

[0053] In formula (5), R 8 represents a hydrogen atom or a methyl group, and n represents an integer of 1 to 3.

[0054] In the formulas (3) to (5), as the formula (3), R is particularly preferably 4 A monomer in which R is methyl and k is 1 is particularly preferred as the formula (4). 5 is a hydrogen atom, R 6 -CH2O-, R 7 A monomer in which m is 1 and R is a hydrogen atom is particularly preferred as the formula (5). 8 A monomer having a methyl group and n being 1.

[0055] (a2) As the monomer represented by the following formula (1), any known monomer may be used.

[0056] [Chemical formula 8]

[0057]

[0058] In formula (1), R 1 represents a hydrogen atom or a methyl group, R 2 represents an aryl group or an alicyclic hydrocarbon group having 3 to 12 carbon atoms.

[0059] In the formula (1), R is particularly preferably 1 Methyl, R 2 A monomer which is an alicyclic hydrocarbon group having 6 carbon atoms.

[0060] (a3) As the monomer represented by the following formula (2), any known monomer may be used.

[0061] [Chemical formula 9]

[0062]

[0063] In formula (2), R 3 It represents an alicyclic hydrocarbon group or an aromatic hydrocarbon group having 3 to 12 carbon atoms.

[0064] In the formula (2), R is particularly preferably 3 A monomer which is an alicyclic hydrocarbon group having 6 carbon atoms.

[0065] The epoxy group-containing polymer can be obtained by copolymerizing at least component (a1), component (a2) and component (a3). The polymerized form may be linear or branched, and may be any of a random copolymer, a block copolymer, a graft copolymer, and the like.

[0066] The polymerization method of the epoxy-containing polymer is not particularly limited, and various polymerization methods such as free radical polymerization, anionic polymerization, plasma polymerization, etc. can be adopted. In addition, polymerization methods such as bulk polymerization, solution polymerization, suspension polymerization, and emulsion polymerization can also be adopted. Furthermore, additives such as catalysts or solvents can also be added to the polymerization reaction system as needed.

[0067] The epoxy equivalent of the epoxy group-containing polymer is 155 to 240 g / mol, preferably 160 to 230 g / mol. By making the epoxy equivalent within the above range, a sufficient cross-linking structure can be obtained and NMP tolerance can be improved.

[0068] The weight average molecular weight (Mw) of the epoxy group-containing polymer is not particularly limited, and is, for example, 3,000 to 100,000, preferably 4,000 to 80,000, and more preferably 10,000 to 50,000.

[0069] As the component (A), in addition to the epoxy group-containing polymer, a multifunctional epoxy resin may be included. The multifunctional epoxy resin may be any epoxy resin having two or more epoxy groups in one molecule, and any known material may be used. Examples of the polyfunctional epoxy resin include bisphenol A epoxy resin, bisphenol A novolac epoxy resin, bisphenol F epoxy resin, brominated bisphenol A epoxy resin, bisphenol S epoxy resin, diphenyl ether epoxy resin, hydroquinone epoxy resin, naphthalene epoxy resin, biphenyl epoxy resin, fluorene epoxy resin, phenol novolac epoxy resin, o-cresol novolac epoxy resin, trihydroxyphenylmethane epoxy resin, trifunctional epoxy resin, tetraphenylolethane epoxy resin, dicyclopentadiene phenol epoxy resin, hydrogenated bisphenol A epoxy resin, bisphenol A core-containing polyol epoxy resin, polypropylene glycol epoxy resin, glycidyl ester epoxy resin, glycidyl amine epoxy resin, glyoxal epoxy resin, alicyclic epoxy resin, heterocyclic epoxy resin, and the like. The multifunctional epoxy resin may be used alone or in combination of two or more. Among them, bisphenol A type, bisphenol A novolac type, and alicyclic type epoxy resins are particularly preferred.

[0070] In 100 parts by mass of the epoxy-containing polymer, the epoxy-containing polymer preferably contains 59.2 to 91.7 parts by mass of the component (a1), preferably contains 3.0 to 35.0 parts by mass of the component (a2), more preferably contains 5.0 to 25.0 parts by mass of the component (a2), and preferably contains 3.0 to 35.0 parts by mass of the component (a3), more preferably contains 5.0 to 25.0 parts by mass of the component (a3).

[0071] The content of the component (A) in 100 parts by mass of the total of the components (A) to (B) is preferably 13 to 87 parts by mass, more preferably 15 to 85 parts by mass, and particularly preferably 23 to 77 parts by mass.

[0072] <(B) Ingredient>

[0073] The component (B) is a vinyl ether blocked polycarboxylic acid obtained by latenting, that is, blocking, the carboxyl groups of the polycarboxylic acid compound as hemiacetal esters with a vinyl ether compound. The component (B) may be used alone or in combination of two or more.

[0074] As the polycarboxylic acid compound, any compound having two or more carboxyl groups in one molecule can be used, and any known material can also be used. As the polycarboxylic acid compound, cyclobutane tetracarboxylic acid, cyclohexane tricarboxylic acid, trimellitic acid, pyromellitic acid, etc. can be listed. Among them, from the perspective of cured film properties such as NMP tolerance, trimellitic acid and pyromellitic acid are preferred. One polycarboxylic acid can be used alone, or two or more can be used in combination.

[0075] The number of carbon atoms of the vinyl ether compound other than the carbon atoms of the vinyl group is preferably 1 to 6, more preferably 2 to 6. Specific examples of the vinyl ether compound include aliphatic vinyl ether compounds such as methyl vinyl ether, ethyl vinyl ether, isopropyl vinyl ether, n-propyl vinyl ether, n-butyl vinyl ether, isobutyl vinyl ether, tert-butyl vinyl ether and cyclohexyl vinyl ether. Among them, n-propyl vinyl ether and isopropyl vinyl ether are preferred from the perspective of being easily available and having a curing temperature suitable for the process of the protective film. In addition, the vinyl ether compound may be used alone or in combination of two or more.

[0076] (B) component can be obtained by reacting a polycarboxylic acid compound with a vinyl ether compound at a temperature in the range of room temperature to 150°C. Since the block reaction is a balanced reaction, when a certain excess of vinyl ether compound is added to the polycarboxylic acid compound, the reaction can be promoted and the yield can be improved. In addition, a catalyst or solvent can be added to the reaction of the polycarboxylic acid compound and the vinyl ether compound according to the purpose. If the acid value of the reaction solution is reduced to less than 2.0 mgKOH / g by the block reaction, it is judged that the reaction is fully carried out, and the reaction is terminated.

[0077] Examples of the catalyst include tertiary amines, imidazoles, organophosphorus compounds, quaternary phosphonium salts, diazabicycloolefins, organometallic compounds, quaternary ammonium salts, boron compounds, and metal halides. The catalyst may be used alone or in combination of two or more.

[0078] Examples of the solvent include aromatic hydrocarbons, ethers, esters, ether esters, ketones, phosphates, nitriles, aprotic polar solvents, and propylene glycol alkyl ether acetates. The solvent may be used alone or in combination of two or more.

[0079] The functional group equivalent ratio of the carboxyl group of the component (B) to the total epoxy group of the component (A) is 0.25 to 0.95, preferably 0.30 to 0.90, and more preferably 0.45 to 0.80. If the functional group equivalent ratio of the carboxyl group to the epoxy group is less than 0.25, sufficient NMP tolerance cannot be obtained, and if it is greater than 0.95, low metal ion residual property is insufficient. By making the ratio of the carboxyl group to the epoxy group within the range described above and combining the component (C) described later, NMP tolerance and low metal ion residual property can be taken into account at a high level.

[0080] <(C) Ingredients>

[0081] As long as the component (C) is an organosilicon surfactant having a polyorganosiloxane skeleton, any known material can be used. Examples of organosilicon surfactants include polyether modified products, polyester modified products, polyol modified products, and special modified products. Among them, polyether modified products are preferred from the perspective of compatibility with other organic materials. However, substances containing fluorine atoms in the structure are not preferred. Examples of commercially available products of the component (C) include BYK-302 (BYK-Chemie JAPAN), BYK-307 (same), BYK-330 (same), BYK-333 (same), BYK-348 (same), BYK-361N (same), BYK-392 (same), BYK-399 (same), POLYFLOW KL-100 (Kyoeisha Chemical Co., Ltd.), KL-400HF (same), KL-401 (same), KL-402 (same), KL-700 (same), LE-304 (same), KP-110 (Shin-Etsu Chemical Co., Ltd. Ltd.), KP-112 (same), KP-323 (same), KP-366 (same), KP-368 (same), KF-351A (same), DISPARLON LS-009 (Kusumoto Chemicals, Ltd.), LHP-91 (same), 1711EF (same), SILFACE SAG003 (Nissin Chemical co., ltd.), SAG005 (same), SAG008 (same), DOWSIL FZ2122 (Dow Toray Co., Ltd.), 8019 (same), 8637, etc. Component (C) may be used alone or in combination of two or more.

[0082] Relative to 100 parts by mass of the total of components (A) and (B), component (C) is 0.01 to 1.0 parts by mass, preferably 0.03 to 0.50 parts by mass, and more preferably 0.05 to 0.20 parts by mass. If component (C) is less than 0.01 parts by mass, sufficient low metal ion residue cannot be obtained, and if it is greater than 1.0 parts by mass, the coating property will be reduced. This new discovery that component (C) not only improves coating property, but also contributes to the improvement of low metal ion residue, thus completing the present invention. In addition, although the reason why low metal ion residue is improved by using component (C) is not clear, it is speculated that this may be because the silicone surfactant segregated on the surface of the cured film inhibits the adsorption of metal ions.

[0083] The weight average molecular weight of the component (C) is preferably 8,000 to 50,000, more preferably 14,000 to 40,000, from the viewpoint of improving low metal ion residual property. When the weight average molecular weight is within the above range, the balance between segregation to the cured film surface and compatibility with other components is excellent.

[0084] The HLB value of the component (C) is preferably 10 or less, and more preferably 3 to 9. The HLB value is defined by the Griffin method.

[0085] <Weight average molecular weight (Mw)>

[0086] The weight average molecular weight of the epoxy group-containing polymer and the component (C) can be determined by GPC. The sample is prepared by dissolving a sample in tetrahydrofuran to prepare a 0.5 wt % solution and filtering the solution through a 0.20 μm membrane filter. The measurement can be performed under the following conditions.

[0087] (Measurement conditions)

[0088] Analytical device: HLC-8320GPC (manufactured by TOSOH CORPORATION)

[0089] Chromatographic column: TSKgel SuperHZM-M (3 pieces) (manufactured by TOSOH CORPORATION)

[0090] Column size: 4.6×150mm

[0091] Eluent: Tetrahydrofuran

[0092] Flow rate: 0.30mL / min

[0093] Detector: Differential refractometer

[0094] Column temperature: 40°C

[0095] Standard sample: polystyrene

[0096] <Other additives>

[0097] The thermosetting resin composition of the present invention may further contain additives such as surfactants other than the surfactant (C), silane coupling agents, antioxidants, stabilizers, and organic solvents within a range that does not hinder the effects of the invention.

[0098] <Silane coupling agent>

[0099] Silane coupling agent is a compound having an alkoxysilyl group (Si-OR) and a reactive group in one molecule. Preferably, the silane coupling agent has an epoxy group as a reactive group. As the silane coupling agent having an epoxy group, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, etc. can be listed. These silane coupling agents can be used alone or in combination of two or more.

[0100] <Antioxidants>

[0101] As the antioxidant, hindered phenol-based antioxidants such as IRGANOX 1010 (BASF), IRGANOX 1035 (same), IRGANOX 1076 (same), IRGANOX 1135 (same), and IRGANOX 1726 (same) can be used.

[0102] <Stabilizer>

[0103] The stabilizer refers to the excess vinyl ether and is added for the purpose of increasing the yield of the carboxylic acid hemiacetal ester. Specifically, the vinyl ethers described in the above "<Component (B)>" are mentioned.

[0104] <Organic solvents>

[0105] The organic solvent is usually added for the purpose of adjusting the viscosity of the thermosetting resin composition, etc. Specifically, there can be mentioned esters such as amyl acetate and butyl acetate; ether esters such as ethyl ethoxy propionate and 3-methoxy-3-methyl-1-butyl acetate; ketones such as methyl ethyl ketone and cyclohexanone; ethylene glycol derivatives such as propylene glycol monomethyl ether acetate, propylene glycol diacetate, and diethylene glycol ethyl methyl ether.

[0106] In addition, if the polarity difference between the pixels of the coloring layer is increased by miniaturizing the pigment contained in the coloring layer of the color filter or increasing the pigment concentration, the protective film forming composition will be segregated on a specific pixel in the process of forming a protective film on the coloring layer, sometimes causing the protective film to bulge and its surface flatness to decrease. Therefore, for the thermosetting resin composition, it is preferred that the flatness when forming a protective film on a coloring layer with a polarity difference between pixels is excellent. From this perspective, the organic solvent preferably includes at least one alicyclic ketone organic solvent selected from cyclopentanone, cyclohexanone, isophorone, etc. The alicyclic ketone organic solvent can be used alone or in combination of two or more.

[0107] Although the mechanism of improving flatness by using an alicyclic ketone organic solvent is not certain, it can be inferred as follows: in the process of forming a protective film on the coloring layer, a protective film-forming composition is applied to the coloring layer, and the organic solvent is removed and then fired. At this time, the polycarboxylic acid hemiacetal ester is decomposed into polycarboxylic acid and vinyl ether by heat, thereby temporarily making the protective film-forming composition highly polarized, and it is inferred that segregation occurs on the high-polarity pixels in each pixel of the coloring layer. Therefore, it is inferred that if an alicyclic ketone organic solvent is present in the protective film-forming composition, the alicyclic ketone organic solvent remaining in a trace amount in the protective film-forming composition will form a coordination structure with the polycarboxylic acid at the high-polarity carbonyl site in the firing process, and the polycarboxylic acid is protected by a cyclic alkyl group that is low in polarity, soft, and shows steric repulsion, thereby suppressing the high polarity of the protective film-forming composition, thereby suppressing the segregation of the protective film-forming composition on specific pixels in each pixel of the coloring layer, and improving flatness.

[0108] When an alicyclic ketone organic solvent is used, the proportion of the alicyclic ketone organic solvent in the organic solvent is preferably 20% by mass or more and 80% by mass or less, more preferably 25% by mass or more and 70% by mass or less, and further preferably 30% by mass or more and 60% by mass or less. In the organic solvent, if the proportion of the alicyclic ketone organic solvent is greater than 80% by mass, the viscosity of the protective film-forming composition will increase, and it will become difficult to apply the coating film with a uniform film thickness. In the organic solvent, if the proportion of the alicyclic ketone organic solvent is less than 20% by mass, it is difficult to obtain the effect of improving flatness.

[0109] (Formation of color filter protective film)

[0110] The color filter of the present invention has a layer of a cured product formed by curing the above-mentioned thermosetting resin composition as a protective film. The thermosetting resin composition is applied so as to cover the coloring layer or black matrix arranged on the substrate. The coating method is not particularly limited, and a known coating method such as an inkjet method, a spin coating method, and a slit coating method can be used.

[0111] The obtained coating film is dried, and further preheated (hereinafter referred to as "pre-baking") as needed, and then subjected to main curing heating (hereinafter referred to as "post-baking") to form a layer of resin cured product. At this time, as pre-baking conditions, 40~140℃, 0~1 hour can be listed, and as post-baking conditions, preferred conditions such as 150~280℃, 0.2~2 hours can be listed. In addition, the heating method at this time is not particularly limited, for example, a curing device such as a closed curing furnace or a tunnel furnace capable of continuous curing can be used. The heating source is not particularly limited, and can be carried out by methods such as hot air circulation, infrared heating and high-frequency heating.

[0112] Example

[0113] The present invention will be specifically described below with reference to Examples and Comparative Examples.

[0114] <Polymerization Example 1: Synthesis of epoxy group-containing polymer (A-1)>

[0115] 76.0 parts by mass of propylene glycol monomethyl ether acetate (PGMEA) as a solvent was added to a four-necked flask equipped with a thermometer, a reflux condenser, a stirrer, and a dropping funnel, and the mixture was heated while being stirred to 84° C. Then, a solution (dropping component) prepared by uniformly mixing 64.0 parts by mass of glycidyl methacrylate (GMA) as the component (a1), 22.0 parts by mass of cyclohexyl methacrylate (CHMA) as the component (a2), 14.0 parts by mass of cyclohexylmaleimide (CHMI) as the component (a3), 6.0 parts by mass of a peroxide polymerization initiator “PERHEXYL O (PHO)” manufactured by NOFCORPORATION as a polymerization initiator, and 18.0 parts by mass of PGMEA was added dropwise at a temperature of 84° C. using a dropping funnel over two hours. Then, the temperature was maintained at 84° C. for 5 hours to obtain a 50% PGMEA solution of an epoxy group-containing polymer (A-1) having a weight average molecular weight (Mw) of 21,200 and an epoxy equivalent of 222 g / mol (calculated as active ingredient).

[0116] <Polymerization Examples 2 to 5: Synthesis of Epoxy-containing Polymers (A-2 to A-5)>

[0117] The raw materials shown in Table 1 were mixed under the conditions shown in Table 1, and polymers A-2 to A-5 were obtained in the same manner as in Polymerization Example 1. Table 1 shows the amount of each raw material added, the weight average molecular weight, and the epoxy equivalent.

[0118] [Table 1]

[0119]

[0120] The abbreviations in Table 1 are as follows. Table 2 shows the details of the components (a1), (a2), and (a3) ​​used.

[0121] (a1)Ingredients

[0122] GMA: Glycidyl Methacrylate

[0123] (a2) Ingredients

[0124] CHMA: Cyclohexyl methacrylate

[0125] DCPMA: Dicyclopentyl methacrylate

[0126] (a3) Ingredients

[0127] CHMI: Cyclohexylmaleimide

[0128] PhMI: phenylmaleimide

[0129] (Polymerization initiator)

[0130] PHO: tert-Hyl peroxy(2-ethylhexanoate) (peroxide-based polymerization initiator manufactured by NOF CORPORATION, "Product name: PERHEXYL O")

[0131] (Solvent)

[0132] PGMEA: Propylene glycol monomethyl ether acetate

[0133] [Table 2]

[0134]

[0135] <Comparative Polymerization Examples 1 to 4: Synthesis of Epoxy-containing Polymers (A'-1 to A'-4)>

[0136] The raw materials shown in Table 3 were mixed under the conditions shown in Table 3, and polymers A'-1 to A'-4 were obtained in the same manner as in Polymerization Example 1. Table 3 shows the amount of each raw material added, the weight average molecular weight, and the epoxy equivalent.

[0137] [Table 3]

[0138]

[0139] The abbreviations in Table 3 are as follows.

[0140] (a1)Ingredients

[0141] GMA: Glycidyl Methacrylate

[0142] (a2) Ingredients

[0143] CHMA: Cyclohexyl methacrylate

[0144] (a3) Ingredients

[0145] CHMI: Cyclohexylmaleimide

[0146] (Polymerization initiator)

[0147] PHO: tert-Hyl peroxy(2-ethylhexanoate) (peroxide-based polymerization initiator manufactured by NOF CORPORATION, "Product name: PERHEXYL O")

[0148] (Solvent)

[0149] PGMEA: Propylene glycol monomethyl ether acetate

[0150] <Synthesis Example 1: Synthesis of (B) Component (B-1)>

[0151] In a four-necked flask equipped with a thermometer, a reflux condenser, and a stirrer, 26.8 parts by mass of propylene glycol monomethyl ether acetate (PGMEA) as a solvent, 26.9 parts by mass of trimellitic acid (TMA) as a polycarboxylic acid, and 46.3 parts by mass of n-propyl vinyl ether (NPVE) as a vinyl ether were added, and heated while stirring to 80° C. Then, stirring was continued while maintaining the temperature, and after confirming that the acid value of the mixture reached 2.0 mgKOH / g or less, the reaction was terminated to obtain a 60% PGMEA solution of polycarboxylic acid hemiacetal ester (B-1) having an acid value of 0.6 mgKOH / g and an acid equivalent of 156 g / mol (effective component conversion).

[0152] <Acid value>

[0153] The acid value was measured by a method in accordance with JIS K0070-1992 "Test methods for acid value, saponification value, ester value, iodine value, hydroxyl value and unsaponifiable matter of chemicals".

[0154] <Synthesis Examples 2-3: Synthesis of polycarboxylic acid hemiacetal esters (B-2-B-3)>

[0155] The raw materials shown in Table 4 were mixed under the conditions shown in Table 4, and reactants B-2 to B-3 were obtained in the same manner as in Synthesis Example 1. Table 4 shows the amount of each raw material added, the acid value, and the acid equivalent.

[0156] [Table 4]

[0157]

[0158] The abbreviations in Table 4 are as follows.

[0159] (Polycarboxylic Acid)

[0160] TMA: trimellitic acid

[0161] PMA: Pyromellitic Acid

[0162] (Vinyl Ether)

[0163] NPVE: n-propyl vinyl ether

[0164] IPVE: Isopropyl Vinyl Ether

[0165] (Solvent)

[0166] PGMEA: Propylene glycol monomethyl ether acetate

[0167] <Examples 1 to 18, Comparative Examples 1 to 8>

[0168] The components shown in Tables 5 to 7 were dissolved and mixed in the blending amounts shown in Tables 5 to 7 to prepare coating solutions of thermosetting resin compositions for color filter protective films of Examples 1 to 18 and Comparative Examples 1 to 8. In addition, in Tables 5 to 7, the numerical values ​​indicating the content of each component are parts by mass. In addition, the abbreviations in Tables 5 to 7 are as follows.

[0169] <(C) Ingredients>

[0170] C-1: DOWSIL 8019 (manufactured by Dow Toray Co., Ltd., polyether modified product, Mw: 19,000)

[0171] C-2: DISPARLON 1711EF (manufactured by Kusumoto Chemicals, Ltd., polyether modified product, Mw: 16,400)

[0172] C-3: SILFACE SAG008 (manufactured by Nissin Chemical Co., Ltd., polyether modified product, Mw: 10,100)

[0173] <Multifunctional epoxy resin>

[0174] EP157: Bisphenol A novolac type epoxy resin (manufactured by Mitsubishi Chemical Corporation, trade name: "jER157S70", epoxy equivalent: 210 g / eq)

[0175] <Other surfactants>

[0176] C'-1: MAGAFACE F-477 (manufactured by DIC CORPORATION, fluorine-based)

[0177] <Stabilizer>

[0178] NPVE: n-propyl vinyl ether

[0179] IPVE: Isopropyl Vinyl Ether

[0180] <Additives>

[0181] NMM: N-methylmorpholine

[0182] <Solvent>

[0183] PGMEA: Propylene glycol monomethyl ether acetate

[0184] BAC: Butyl Acetate

[0185] After filtering the coating liquid of the thermosetting resin composition of Examples 1 to 18 and Comparative Examples 1 to 8 using a membrane filter (material: PE, pore size: 0.2 μm), it was further filtered using a hollow filter (material: PP, pore size: 0.02 μm). Using a spin coater (model 1H-DX-2, manufactured by MIKASA CO., LTD), the coating liquid of the thermosetting resin composition for the obtained color filter protective film was spin-coated on the substrate. After coating, the substrate was pre-baked in a clean oven at 90°C for 2 minutes, and then post-baked in a clean oven at 230°C for 30 minutes to obtain a cured film of a specified film thickness. The thermosetting resin composition or the obtained cured film was evaluated for "low metal ion residue" and "NMP tolerance" as shown below. In addition, the coating liquid of the thermosetting resin composition of Examples 1 to 18 and Comparative Examples 1 to 8 was evaluated for "coating properties" as shown below. The evaluation results are shown in Tables 5 to 7.

[0186] <Low metal ion residue>

[0187] An alkali-free glass substrate (EAGLE XG, manufactured by Corning Incorporated) having a 1.0 μm-thick cured film formed thereon was irradiated with a UV cleaning device (EYE UV-ozone cleaning device, manufactured by IWASAKI ELECTRIC CO., LTD.) at a dose of 5,000 mJ / cm 2 After UV-ozone irradiation (254nm conversion), it was immersed in 0.05wt% potassium hydroxide developer for 60 seconds. Then, the substrate was cleaned with pure water for 10 seconds, and the substrate was fully dried by blowing. Using a fluorescent X-ray device (ZSX100e, Rigaku Corporation manufactured), the residual potassium amount on the cured film surface of the substrate was measured. The situation where the residual potassium amount was less than 0.4% was evaluated as ◎, the situation where it was greater than 0.4% and less than 0.6% was evaluated as 0, and the situation where it was greater than 0.6% was evaluated as ×. The situation where the residual potassium amount was ◎ or 0 was set as qualified.

[0188] <NMP resistance>

[0189] 100 μL of NMP was dripped onto a 10 cm square alkali-free glass substrate (EAGLE XG, manufactured by Corning) with a 1.0 μm thick cured film, and after covering it with an 8 cm square cover glass, it was heated at 180°C for 15 minutes. After the heating was terminated, the cover glass was removed and the NMP on the surface of the cured film was removed by blowing. The film thickness of the cured film before and after the test was measured, and the film thickness change rate was calculated. The case where the film thickness change rate before and after the test was less than 25% was evaluated as ◎, the case where it was greater than 25% and less than 30% was evaluated as 0, and the case where it was greater than 30% was evaluated as ×. The case where the film thickness change rate before and after the test was ◎ or 0 was regarded as qualified.

[0190] <Coating properties (spin coating)>

[0191] The coating liquid of the thermosetting resin composition was coated on a 10 cm square alkali-free glass substrate (EAGEL XG, manufactured by Corning) so that the film thickness after curing was 1.0 μm, and then allowed to stand for 5 minutes under an environment of 23°C × 50% RH. After standing, the case where no liquid return was observed at the start of coating was evaluated as ◎, the case where the maximum width of the liquid return was less than 2 mm was evaluated as 0, and the case where the maximum width of the liquid return was 2 mm or more was evaluated as ×. The case where the liquid return was ◎ or 0 was considered acceptable.

[0192] <Coating properties (slit coating)>

[0193] The coating liquid of the thermosetting resin composition was applied using an applicator at a distance of 2 cm from one side of a 10 cm square alkali-free glass substrate (EAGEL XG, manufactured by Corning) to a condition where the film thickness after curing reached 1.0 μm, and then allowed to stand for 5 minutes under an environment of 23°C×50%RH. The case where no liquid return was observed at the start of coating after standing was evaluated as ◎, the case where the maximum width of the liquid return was less than 2 mm was evaluated as 0, and the case where the maximum width of the liquid return was 2 mm or more was evaluated as ×. The case where the liquid return was ◎ or 0 was considered qualified.

[0194] [Table 5]

[0195]

[0196] [Table 6]

[0197]

[0198] [Table 7]

[0199]

[0200] According to the results of Table 5 and Table 6, in Examples 1 to 18, the low metal ion residue and NMP tolerance of the cured film are good, and the coating property of the coating solution of the thermosetting resin composition is good regardless of the coating method. On the other hand, according to the results of Table 7, since the (C) component is not used in Comparative Examples 1 to 2, the low metal ion residue and coating property are insufficient. In addition, in Comparative Examples 3 to 6, since the (A) component is an epoxy-containing polymer different from the composition of the present invention, the NMP tolerance is insufficient. Further, in Comparative Examples 7 to 8, since the functional group equivalent ratio of the carboxyl group of the (B) component to the epoxy group in the (A) component is too large or too small, the low metal ion residue or NMP tolerance is insufficient.

[0201] <Examples 19 to 42>

[0202] The components shown in Tables 8 to 10 were dissolved and mixed in the blending amounts shown in Tables 8 to 10 to prepare coating solutions of thermosetting resin compositions for color filter protective films of Examples 19 to 42. In addition, in Tables 8 to 10, the numerical values ​​indicating the content of each component are parts by mass. In addition, except for the following abbreviations, the abbreviations in Tables 8 to 10 are the same as those in Tables 5 to 7.

[0203] CHN: Cyclohexanone

[0204] CPN: Cyclopentanone

[0205] The coating liquid of the thermosetting resin composition of Examples 19 to 42 was filtered using a membrane filter (material: PE, pore size: 0.2 μm), and then further filtered using a hollow filter (material: PP, pore size: 0.02 μm). The coating liquid of the thermosetting resin composition for the obtained color filter protective film was spin-coated on the substrate using a spin coater (model 1H-DX-2, manufactured by Mikasa Corporation). After coating, the substrate was pre-baked in a dust-free oven at 90°C for 2 minutes, and then post-baked in a dust-free oven at 230°C for 30 minutes to obtain a cured film of a specified film thickness. The thermosetting resin composition or the obtained cured film was evaluated for the above-mentioned "low metal ion residue", "NMP resistance" and the following "flatness (pattern substrate)", "flatness (color filter substrate)". In addition, the above-mentioned "coating property" was evaluated using the coating liquid of the thermosetting resin composition of Examples 19 to 42. The evaluation results are shown in Tables 8 to 10.

[0206] <Flatness (Pattern Substrate)>

[0207] After forming a 1.0 μm thick cured film on a pattern substrate with L / S=150μm / 50μm and a height of 2.5μm, the surface step difference was measured using a probe-type surface roughness meter (model EK4000AK, manufactured by Kosaka Laboratory Ltd.). The flattening rate X was calculated by the following calculation formula (1) from the maximum height difference (d1) of the pattern substrate before the formation of the cured film and the maximum height difference (d2) after the formation of the cured film. The flattening rate before and after the test was evaluated as ◎ for a case of more than 85%, 0 for a case of more than 80% and less than 85%, and × for a case of less than 80%. The flattening rate before and after the test was ◎ or 0, which was qualified.

[0208] [Mathematical formula 1]

[0209]

[0210] <Flatness (Color filter substrate)>

[0211] The virtual color filter used for flatness evaluation is used to calculate the height difference between the red pixel and the green pixel center, the height difference between the red pixel and the blue pixel center, and the height difference between the green pixel and the blue pixel center (pixel step difference). After forming a 1.0 μm thick cured film on the color filter substrate, the height difference between the red pixel and the green pixel center, the height difference between the red pixel and the blue pixel center, and the height difference between the green pixel and the blue pixel center of the same part are calculated. These step differences are measured by a probe-type surface roughness meter (model EK4000AK, manufactured by Kosaka Laboratory Ltd.). The maximum value of the pixel step difference before the formation of the cured film is set as the maximum pixel step difference before coating (d1), and the maximum value of the pixel step difference after the formation of the cured film is set as the maximum pixel step difference after coating (d2). The flattening rate X is calculated from these d1 and d2 by the following calculation formula (1). The flattening rate before and after the test was 85% or more and was evaluated as ◎, the flattening rate before and after the test was 80% or more and less than 85% and less than 80%. The flattening rate before and after the test was ◎ or 0, and the result was considered acceptable.

[0212] [Mathematical formula 1]

[0213]

[0214] [Table 8]

[0215]

[0216] [Table 9]

[0217]

[0218] [Table 10]

[0219]

[0220] According to the results of Tables 8 to 10, in Examples 19 to 41, the low metal ion residue and NMP resistance of the cured film, and the flatness were good, and the coating properties of the coating solution of the thermosetting resin composition were good regardless of the coating method. In Example 42, the low metal ion residue and NMP resistance of the cured film, and the flatness of the pattern substrate were good, and the coating properties of the coating solution of the thermosetting resin composition were good regardless of the coating method, but since the alicyclic ketone organic solvent was not used as the organic solvent, the flatness of the color filter substrate was insufficient.

Claims

1. A thermosetting resin composition comprising an epoxy compound (A), a polycarboxylic acid hemiacetal ester (B), and a silicone surfactant (C), characterized in that: The epoxy compound (A) comprises an epoxy group-containing polymer having (a1) a (meth)acrylate monomer having an epoxy group, (a2) a monomer represented by the following formula (1), and (a3) ​​a monomer represented by the following formula (2) as structural units and having an epoxy equivalent of 155 to 240 g / mol, [Chemical formula 1] In formula (1), R 1 represents a hydrogen atom or a methyl group, R 2 represents an aromatic group or an alicyclic hydrocarbon group having 3 to 12 carbon atoms, [Chemical formula 2] In formula (2), R 3 represents an alicyclic hydrocarbon group or an aromatic hydrocarbon group having 3 to 12 carbon atoms, The amount of the silicone surfactant (C) is 0.01 to 1.0 parts by mass relative to 100 parts by mass of the total of the epoxy compound (A) and the polycarboxylic acid hemiacetal ester (B). The functional group equivalent ratio of the carboxyl groups of the polycarboxylic acid hemiacetal ester (B) to the total epoxy groups of the epoxy compound (A) is in the range of 0.25 to 0.

95.

2. The thermosetting resin composition according to claim 1, characterized in that The thermosetting resin composition further comprises an organic solvent, Among the organic solvents, the ratio of the alicyclic ketone organic solvent is 20% by mass or more and 80% by mass or less.

3. A color filter, characterized in that: The color filter has a protective film formed by curing the thermosetting resin composition according to claim 1 or 2.

Citation Information

Patent Citations

  • Resin composition for color filter protective film, and color filter

    JP2011065051A

  • Thermosetting resin composition and color filter having hardened film of the same

    JP2022026360A

  • Thermosetting resin composition and color filter having cured film thereof

    JP2022112451A